2003
DOI: 10.1088/0967-3334/24/1/312
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of bone mineral content by x-ray microtomography

Abstract: A new non-destructive method based on x-ray microtomography (micro-CT) was developed to measure calcium density in bone. X-ray micro-CT was used as a quantitative approach to acquire and reconstruct virtual cross-sections through the sample. Accurate beam-hardening correction was implemented. Grey values in the virtual cross-sections were calibrated as calcium mineral density in bone. From these cross-sections, three-dimensional models were created. Calcium content was calculated directly from images and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 27 publications
2
57
0
2
Order By: Relevance
“…To examine the effects of exemestane treatment on whole bone parameters and on the trabecular bone in particular, right femora were analyzed by high-resolution X-ray micro-CT. Micro-CT has been shown to be well suited for the nondestructive visualization and quantitative analysis of bone and calcified tissue [20,21]. …”
Section: Experimental Designmentioning
confidence: 99%
“…To examine the effects of exemestane treatment on whole bone parameters and on the trabecular bone in particular, right femora were analyzed by high-resolution X-ray micro-CT. Micro-CT has been shown to be well suited for the nondestructive visualization and quantitative analysis of bone and calcified tissue [20,21]. …”
Section: Experimental Designmentioning
confidence: 99%
“…Degeneration of tissues in microgravity is a serious obstacle for long-term human stays in space or for interplanetary flights. It has been found that a stay under these conditions leads to bone demineralization (Postnov et al, 2003;Swinerd, 2008). Changes in the concentration of other heavier elements can also be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers assume that X-ray absorption in the demineralized portion of bone is constant. 62 Similar assumptions can be made about the demineralized portion of dentin. Resin has been used by several authors as a soft tissue equivalent for the fabrication of radiographic phantoms, 55,[63][64][65] but the non-uniform distribution of powder during the mixing and resin curing processes 66 has resulted in grainy radiographic images.…”
Section: Measurements and Calibrationsmentioning
confidence: 94%